Spatial and Temporal Variation of Drought in Far and Mid Western Regions of Nepal: Time Series Analysis (1982-2012) - Kafle, Hemu Kharel (Nepal Journal of Science and Technology, 2015)
Recent and potential future increases in global temperature are likely to be associated with impacts on the hydrological cycle, including changes to precipitation and increases in extreme events such as droughts. This study has investigated the spatial and temporal changes in drought occurrence in far and mid-western regions of Nepal. Quantification of the severity and frequency of drought within different physiographical regions have been worked out with the help of Standardized Reconnaissance Drought Index (RDIst). Time series analyses of mean annual rainfall and annual temperature datasets of 16 meteorological stations covering far and mid western development regions from 1982-2012 have been used. It has been revealed that all the three kinds (moderate, severe and extreme) of droughts occurred in the study area. Extreme drought was recorded in four stations (Dadeldhura, Patan, Tikapur and Silgadhi) of far west region and five stations (Musikot, Dailekh, Surkhet, Tulsipur and Khajura) of mid western region. These events occurred when precipitation recorded its lowest range. Most frequent droughts were observed in Dhangadhi, Dadeldhura and Jumla. There were higher number of droughts in far western region but more extreme events occurred in mid western region. No clear correlation was found between temperature and precipitation trends in five selected stations except in Dhangadi that lies in Terai region. DOI: http://dx.doi.org/njst.v15i2.12118 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 65-76